Perpustakaan sebagai Organisasi Sumber Belajar - Ashari, Ashari (Pustakaloka, 2009)
Library management as a learning source is simply explained emphasize the understanding of library role in learning process. It is important because the society appreciation towards the significant library role in educational institution is still very low. This article is going to awaken the emphaty of all stakeholders in connection with library development and management to make an effort to enhance library services percisly.